Development of semicircular canal occlusion - Fei, Su; Guangfei, Li; Jie, Meng; Yiling, Gao; Mingjing, Cai; Qingxiang, Zhang; Wei, Meng; Shuangba, He (Frontiers in Neuroscience, 2022)
Surgical treatment of vertigo is performed with in-depth study of inner ear diseases. Achieving an effective control of vertigo symptoms while reducing damage to hearing and reducing surgical complications is the principle followed by scholars studying surgical modalities. Semicircular canal occlusion is aimed at treatment of partial peripheral vertigo disease and has attracted the attention of scholars because of the above advantages. This article provides a review of the origins of semicircular canal obstruction, related basic research, clinical applications, and the effects of surgery on vestibular and hearing function.